2016
DOI: 10.1007/s10614-016-9565-4
|View full text |Cite
|
Sign up to set email alerts
|

Extremal Pure Strategies and Monotonicity in Repeated Games

Abstract: The recent development of computational methods in repeated games has made it possible to study the properties of subgame-perfect equilibria in more detail. This paper shows that the lowest equilibrium payoffs may increase in pure strategies when the players become more patient and this may cause the set of equilibrium paths to be non-monotonic. A numerical example is constructed such that a path is no longer equilibrium when the players' discount factors increase. This property can be more easily seen when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…In general, the set of equilibrium payoffs needs not be monotone in the discount factor [25,32,39]. However, if the set of continuation payoffs is convex, e.g., if correlated strategies are available, then the payoff set is monotone in the discount factor [2].…”
Section: From This Condition We Getmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the set of equilibrium payoffs needs not be monotone in the discount factor [25,32,39]. However, if the set of continuation payoffs is convex, e.g., if correlated strategies are available, then the payoff set is monotone in the discount factor [2].…”
Section: From This Condition We Getmentioning
confidence: 99%
“…This method has only been implemented in specific situations and it has not been implemented in general games. One difficulty in computing equilibria is finding the optimal punishment payoffs and strategies (see [25,26], where pure-strategy punishments are studied). This is an open problem, and we assume that the punishment payoffs are known.…”
Section: Introductionmentioning
confidence: 99%
“…The punishment payoffs are v − (V (T 1 )) and v − (V (T 2 )). Complementing the following result, it is shown in [7] that the equilibrium paths may not be monotone in the discount factor if the punishment payoffs increase. Note also that the monotonicity of paths holds even though the equilibrium payoffs may fail to satisfy the monotone comparative statics.…”
Section: Properties Of Elementary Subpathsmentioning
confidence: 67%
“…We shall derive a characterization for the equilibrium subpaths by assuming that the players' smallest equilibrium payoffs are known. Finding these payoffs is discussed in Section 4.1, see also [7,11] on the computation of the smallest equilibrium payoffs.…”
Section: Notation and Definitionsmentioning
confidence: 99%
“…We leave for future research how the minimum payoffs should be found. It is not an easy task even in repeated games [10,11], but these methods can be generalized to stochastic games. For an upper bound, we can solvẽ…”
Section: Elementary Subpathsmentioning
confidence: 99%